Analysis of The Impact of Riba Nasi'ah Practices on Digital Consumer Protection and Sharia Business Ethics of Halal Cake Umkm in E-Commerce - Helvinasari Nasution; Muhammad Irwan Padli Nasution; Muhammad Habibi Siregar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The development of the digital culinary ecosystem through e-food delivery applications encourages the use of paylater features that offer payment convenience, but potentially contain elements of riba nasi'ah in the form of additional fees for delayed payments. This practice raises issues from the perspective of digital consumer protection and Islamic business ethics. This study analyzes the impact of riba nasi'ah practices on digital consumer protection and Islamic business ethics in halal cake MSMEs in the e-commerce ecosystem. This study addresses the issue of hidden interest mechanisms embedded in digital financial features such as buy now pay later (BNPL) and fintech-based loans, which are contrary to Islamic principles. The research questions focus on how riba nasi'ah affects Islamic business ethics and digital consumer protection, and what Sharia-based solutions can be implemented. This study uses a qualitative normative-conceptual approach based on a literature review of reputable journals, books, and regulatory sources. The findings indicate that riba nasi'ah practices lead to violations of justice (adl), honesty (sidq), and virtue (ihsan), increase production costs, reduce product quality, and weaken consumer trust. Furthermore, these practices create risks of gharar and tadlis in digital transactions. This study contributes by offering an integrative framework that links riba nasi’ah, Islamic business ethics, and consumer protection, and proposes sharia-compliant solutions such as murabahah and wakalah contracts.